Progesterona injetável na sincronização da ovulação de vacas Bos indicus - Carvalho, Laís Reis (2022)
Ovulation synchronization protocols are well established, which allowed them to be routinely used to induce a return to cyclicity in postpartum beef cattle females. In such protocols, mostly, intravaginal devices are used as an exogenous source of P4. Other exogenous sources of P4 have been described in the literature, however, with inconclusive results and little use. Thus, considering the practical, environmental and health benefits that the use of P4i can entail replacing the P4 intravaginal device, in addition to limited studies carried out on this subject, the objective of the study was to evaluate different doses of injectable progesterone (P4i) and its efficiency in a new ovulation synchronization protocol using P4i as a replacement for intravaginal implantation of P4 in Bos indicus cows. Five experiments were carried out in total. To determine the P4 release curve (Experiment 1), 55 Nellore cows were used. Females were divided into 5 experimental groups for administration of different doses of P4i on D0 (P4i60mg, n=11; P4i105mg, n=11; P4i150mg, n=11; P4i195mg, n=11 and P4i240mg, n=11) and were submitted to the ovulation synchronization protocol (D0: P4i+EB; D8: PGF2α+EC+eCG). Daily blood samples (D0 to D12) were collected for analysis of the serum P4 profile by puncture of the jugular vein. To evaluate ovarian follicular dynamics and the timing of ovulation, three experiments were performed with different doses of P4i at the beginning of the ovulation synchronization protocol (Experiment 2: 150mg and 105mg of P4i; Experiment 3: 75mg of P4i; Experiment 4: 60mg of P4i). After administration of the ovulation inducer, ultrasound examinations were performed every 24 hours until 96 hours later or until ovulation occurred in the animals. To assess the pregnancy rate (Experiment 5), 132 Bos indicus cows were submitted to the ovulation synchronization protocol using 75mg P4i (P4i75 group) or P4 intravaginal device (control group) on D0. The pregnancy diagnosis and the cyclicity rate were performed 30 days after the FTAI (D40). In the P4i release curve, it was observed that the peak occurred one day after the treatments (D1) for the different doses of P4i administered and, from D3 onwards, all groups remained with concentrations below 1ng/mL until the end of the study (D12). Regarding ovarian follicular dynamics, the dose of 75mg showed an ovulation rate at the end of the ovulation synchronization protocol similar to the control group. However, the pregnancy rate was higher in cows in the Control group. Therefore, the administration of P4i at the beginning of the FTAI protocol in Bos indicus cows presents inferior fertility results compared to the P4 intravaginal device.